Nano Radio and RoF Applications - S. Pipatsart; A. Afroozeh; J. Ali; P.P. Yupapin (My University, 2012)
A new design of THz frequency carrier generation for radio frequency identification (RFID) application is proposed. The dense wavelength division multiplexing can be generated and obtained by using a Gaussian or soliton pulses propagating within a modified add-drop filter known as a PANDA ring resonator. The broad bandwidth of THz signals can be obtained and available for useful applications, in which the use of the generated THz pulses for RFID application, for instance, Ad-Hoc network using RFID. Results obtained have shown that the increasing in channel capacity can be obtained and useful for the large demand of RFID applications.
Keywords: Channel spacing; Photonic and Optical Devices